Potential Development of Bioindustry in Cattle and Oil Palm Integration System - Gunawan .; Chalid Talib (Indonesian Center for Animal Research and Development, 2014)
An integrated system between cattle and oil palm plantation has a great potency for development of bioindustry, either in the form of animal feed or organic fertilizer bioindustry. Bioindustry of cattle feed is developed from biomass of plantations, such as stem and leaves of palm, palm kernel and solid. Bioindustry of organic fertilizer is developed from cattle manure. The targets of development of bioindustry are palm plantations in Sumatera and Kalimantan regions, covering 9.25 million hectares. It is estimated to be able to produce biomass quantity as much as 54.60 million tons per year which can be used as fodder for 12.13 million animal unit (AU) of beef cattle, whereas currently there are only 3.06 million AU cattle in Sumatera and Kalimantan, so the opportunities for the addition of cattle in both islands are 9.07 million AU. The existing beef cattle population of 3.06 million AU has the potency to produce 6.1 million tons of organic fertilizer can be used to fertilize 3.0 million hectares, therefore the rest of 6.25 million hectares remain unfertilised. The prospect of bioindustries on integration system of cattle with oil palm plantations in Sumatera and Kalimantan is very potential to meet the needs of organic fertilizer for plants and to utilize oil palm biomass for cattle feed. Key words: Bioindustry, biomass of oil palm plantation, cattle manure